Effect of Ethyl Oleate Pretreatment on Drying of Ginger: Characteristics and Mathematical Modelling - A. Waheed Deshmukh; Mahesh N. Varma; Chang Kyoo Yoo; Kailas L. Wasewar (Journal of Chemistry)
Ginger is of high value and export oriented commodity crop, which plays an important role in agricultural sector. Proper drying techniques are required to capitalize this crop. In the present study, the effect of chemical pretreatment of alkaline ethyl oleate on drying behaviour of ginger was investigated and compared with untreated ginger at selected temperatures of 45, 55, and 65°C at a constant air velocity of 1.8 m/s. The drying rate curves showed that drying occurred in falling rate period and the drying times of pretreated ginger were shorter than those of untreated ginger. Thin-layer drying models such as Newton, Page, Modified Page, Henderson and Pabis, and Wang and Singh were evaluated based on statistical criteria. The Page model was found to be a better model for describing the drying kinetics of the ginger. The rehydration capacity of pretreated sample was more than that of untreated sample and increased with drying temperature. The transport of water during drying was temperature dependent and described by Fick’s equation. The effective diffusivity varied from to  m2/s and to  m2/s with drying temperature for untreated and pretreated ginger slices, respectively.